Erotic fantasy - Döpp, Hans-Jürgen, 1940- (Temporis collection., 2012)
Numerous and diverse points of view come together in this work, demonstrating the multiple aspects that sexuality can present. If nothing is more natural than sexual desire, it is nothing less than the forms by which this desire is expressed and found to satisfy. This book invites you on a special journey, into the universe of emotion, of pleasure and desire.